2023
DOI: 10.36227/techrxiv.21915195.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UTransBPNet: A General Deep Learning Model for Cuffless Blood Pressure Estimation under Activities

Abstract: <p>Cuffless blood pressure (BP) monitoring has gained great attention in the past twenty years considering its significant benefits in cardiovascular healthcare. However, the main challenge of this technology is the inaccurate BP modeling under activities, i.e., existing work have either been inappropriately validated with sufficient intra-individual BP variations, or did not show promising estimation accuracy under activities. In this study, a novel deep learning model <em>UTransBPNet</em>, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Therefore, we have reported the accuracy of ABP to cater to this critical requirement. However, we also recognize that other clinical settings may prioritize discrete measurements of SBP, DBP, and MBP over continuous waveforms, and many previous studies have only reported the prediction performance of models for SBP and DBP [8,16] . To facilitate a broader comparison with existing research, we have included performance metrics for both SBP and DBP predictions in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, we have reported the accuracy of ABP to cater to this critical requirement. However, we also recognize that other clinical settings may prioritize discrete measurements of SBP, DBP, and MBP over continuous waveforms, and many previous studies have only reported the prediction performance of models for SBP and DBP [8,16] . To facilitate a broader comparison with existing research, we have included performance metrics for both SBP and DBP predictions in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Another study proposed a lightweight deep learning model, KD-informer, and accurately predicted continuous BP on two separate datasets, but the intra-subject BP variations were not reported [8] . Additionally, a recent study assessed several machine learning models such as ridge regression, SVM, AdaBoost, and random forest, as well as deep learning methods including VGGNet16, ResNet50, BiLSTM, and ResLSTM, on a large-scale dataset gathered from 3,077 individuals without severe cardiovascular diseases using smartwatches [16] . They reported that the best-performing calibration-free model had estimation errors of -0.71 ± 13.04 and -0.29 ± 8.78 mmHg for SBP and DBP, respectively.…”
Section: Introductionmentioning
confidence: 99%